PENGARUH MEDIA PEMBELAJARAN PAPAN BAKI (BAGI DAN KALI) TERHADAP PEMAHAMAN MATEMATIS SISWA PADA MATERI OPERASI HITUNG PEMBAGIAN DAN PERKALIAN BILANGAN CACAH: (Penelitian Eksperimen pada Siswa Kelas II SDN Paniis Kecamatan Tanjungkerta Kabupaten Sumedang Tahun Pelajaran 2021/2022) - An Nisa Suryani; Handayani, Hani; akbar, aulia (LPPM UNSAP & Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research is motivated by the low mathematical understanding of students on the material of division and multiplication. This study is intended to determine the effect of BAKI board learning media on students mathematical understanding of the material for arithmetical operations division and multiplication of whole numbers. The method used in this research is an experiment with a research design One-Group Pretest-Posttest Design. The data collection technique used was a written test with 5 PG questions and 3 essay questions. The subjects in this study were second grade students of SDN Paniis which consisted of 10 people.Based on the results of the calculation of the pretest and posttest data through the t-test of 10 students, the average value was 18.7, standard deviation was 15.15, = 3.90 and = 2.2622. Thus it shows that -= -2.2622 = 3.90 = 2.2622 so that it is rejected and accepted. Thus, it can be concluded that there is an influence of BAKI board learning media (division and multiplication) on the mathematical understanding of arithmetic operations, division and multiplication of whole numbers in grade II students of SDN Paniis in the 2021/2022 academic year